Human rights abuses against internally displaced persons (IDPs) in Nigeria: investigating media reportage (2020)
This chapter investigates media reportage of human right abuses and sexual violence against internally displaced persons (IDPs) in Nigeria. Using the social responsibility theory, it analyses how the media frames, prominence, slant and whether the Nigeria media employed investigative reports in its reportage of human rights abuses against IDPs. The chapter through a quantitative content analysis of 157 editions of two purposely selected newspapers (the Vanguard NG and the Daily Trust), found that the media failed to contextualise the stories in relation to its causes, solutions and in identifying perpetrators for justice to be served, similarly, the media took sides with victims of the violations. It also failed to accord the required prominence and necessary investigative touch to such stories. It is recommended that there should be frequent trainings for journalists so as to safeguard professionalism in the industry.